Влияние структурных изменений при высокотемпературном нагреве на характеристики пластичности никелевых сплавов - Звягинцева, А.В.; Ющенко, К.А.; Савченко, B.C. (Автоматическая сварка, 2001)
Investigation of hot ductility of alloy IN 840 proves that it has three characteristic ductility temperature ranges. Drastic fall in ductility takes place in a narrow temperature range. It results from melting of grain boundaries to form on them small amounts of the liquid films. The data of metallography and fractography obtained on welded samples show that fracture at high temperatures occurs along the boundaries of grains (dendrites) rich in alloying elements and is of the same nature as fracture of the base metal at high temperatures.